2016
DOI: 10.1249/mss.0000000000001062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Standing and Light-Intensity Walking and Cycling on 24-h Glucose

Abstract: Replacing sitting with regular intervals of standing or light-intensity activity during an 8-h workday reduces 24-h and postprandial glucose. These effects persist during evening hours, with CYCLE having the largest and most sustained effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 46 publications
1
86
2
Order By: Relevance
“…They found the exercise intensity during exergaming to be significantly higher than  during sedentary computer games; however, the intensity of the exergames was comparable with bowling13 and significantly lower than of treadmill walking or jogging 12. Even if low-intensity activities might attenuate the detrimental effects of prolonged sitting,20 we argue that activities of moderate and high intensities should be advocated to achieve superior health benefits. Maintaining a good cardiorespiratory fitness over years is strongly and independently associated with improved health outcomes and survival 21 22.…”
Section: Discussionmentioning
confidence: 65%
“…They found the exercise intensity during exergaming to be significantly higher than  during sedentary computer games; however, the intensity of the exergames was comparable with bowling13 and significantly lower than of treadmill walking or jogging 12. Even if low-intensity activities might attenuate the detrimental effects of prolonged sitting,20 we argue that activities of moderate and high intensities should be advocated to achieve superior health benefits. Maintaining a good cardiorespiratory fitness over years is strongly and independently associated with improved health outcomes and survival 21 22.…”
Section: Discussionmentioning
confidence: 65%
“…While the meta-analysis showed that interrupting prolonged sitting with short periods of standing did not appear to be a sufficient activity to induce acute benefits, this conclusion was based on only two studies. One more recent experimental study of overweight adults showed that replacing 2.5 hours of sitting with standing, over the course of a simulated 8-hr workday, was associated with significant improvements in blood pressure and glucose (19, 79). …”
Section: Observational Epidemiologic Studies Linking Sedentary Behavimentioning
confidence: 99%
“…While using a treadmill, work‐hour HR was higher compared with seated or standing , which is normal since a treadmill requires the use of large muscle groups. However, one study reported that the use of treadmill desk did not seem to modify this variable on the long run because HR measurements at 3 and 9 months were no different than at baseline .…”
Section: Resultsmentioning
confidence: 99%
“…Standing desks can also positively impact glycemic control through improved plasma glucose (work‐hour, post‐work‐hour, and 24‐hour), fasting glucose, beta cell function, and mean insulin area under the curve . One study also reported improvements in 6‐hour postprandial, as well as breakfast and dinner, interstitial glucose .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation